1999
DOI: 10.1007/s002940050489
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of mitochondrial DNA escape to the nucleus in the yeast Saccharomyces cerevisiae

Abstract: The transfer of organelle nucleic acid to the nucleus has been observed in both plants and animals. Using a unique assay to monitor mitochondrial DNA escape to the nucleus in the yeast Saccharomyces cerevisiae, we previously showed that mutations in several nuclear genes, collectively called yme mutants, cause a high rate of mitochondrial DNA escape to the nucleus. Here we demonstrate that mtDNA escape occurs via an intracellular mechanism that is dependent on the composition of the growth medium and the genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Thorsness and colleagues used a unique assay for the escape of mitochondrial genes into the nucleus to demonstrate a requirement for vacuolar proteases. Since they were also able to show that the process is cell-autonomous, i.e., does not proceed via cell lysis and uptake of mitochondrial DNA into neighboring cells (104), these data are consistent with the contention that autophagy is a major regulated pathway for mitochondrial breakdown (16). The fact that mutants that compromise mitochondrial function also increase mitochondrial DNA escape into the nucleus also suggests that defective mitochondria are selectively targeted.…”
Section: Mitochondrial Recyclingsupporting
confidence: 75%
“…Thorsness and colleagues used a unique assay for the escape of mitochondrial genes into the nucleus to demonstrate a requirement for vacuolar proteases. Since they were also able to show that the process is cell-autonomous, i.e., does not proceed via cell lysis and uptake of mitochondrial DNA into neighboring cells (104), these data are consistent with the contention that autophagy is a major regulated pathway for mitochondrial breakdown (16). The fact that mutants that compromise mitochondrial function also increase mitochondrial DNA escape into the nucleus also suggests that defective mitochondria are selectively targeted.…”
Section: Mitochondrial Recyclingsupporting
confidence: 75%
“…29,30 Furthermore, in yeast, impairment of the Yme1p-mediated degradation of Cox2p subunits that are not correctly assembled in cytochrome c oxidase complex of the respiratory chain, leads to mitochondrial degradation by a poorly characterised process. 31,32 As already stated, Dfmc1 cells grown at nonpermissive temperature are known to accumulate a-F1 and b-F1 aggregates in the mitochondrial matrix. 22 A tempting hypothesis would, therefore, be that the autophagic process depicted here could result from a similar signalling initiated by these matricial aggregates.…”
Section: Resultsmentioning
confidence: 81%
“…These studies showed that (i) any segment of an organellar genome can be transferred to the nucleus, and (ii) that large norgDNAs exist that span several genes or even entire organellar chromosomes [6,7,14,15,22,25,26]. Moreover, analysis of human NUMTs has provided no evidence for splicing or polyadenylation of organellar nucleic acids before insertion [14], indicating that migration of mtDNA sequences to the nucleus is predominantly DNA mediated.…”
Section: Genomic Organization Of Norgdnasmentioning
confidence: 99%